Bank Sampah Sebagai Upaya Pemberdayaan Masyarakat - Reni Sri Hapsari; Eddy Suwasono; Ahsin Daroini (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
A waste bank is a place that is used to collect garbage that has been sorted. while Waste Bank Management uses a system such as Banking This study aims to find out about 1) General description of waste bank "Benefits" 2) Impact of community empowerment through waste bank "Benefits" 3) Management of "Benefit" Waste Bank Management in Bolorejo Village, 4) Community Empowerment Implementation conducted by Waste Bank Management This study uses a qualitative descriptive approach with the research location in the "Benefit" Waste Bank located in Bolorejo Village, Tulungagung Regency. Research conducted by using interview, observation, and documentation guidelines The results of the study show that: 1) General description of the waste bank "Benefits" Bolorejo village community is more motivated and motivated to create a clean environment, and the life behavior of caring and cultured citizens 2) Impact of community empowerment through waste banks "Benefits" in the visible environmental aspects from the cleaner environment, the economic aspects can provide additional income for active members, and on the social aspects increasingly familiarize between communities. 3) Management of "Benefit" Garbage Banks in Bolorejo Village Benefit Bank is managed by 7 administrators who serve as Chair, Secretary, Treasurer, Teller, Sorting, Weighing and Packing 4) Implementation of community empowerment through waste banks in the Waste Bank "Benefits" Bolorejo Village has activities that include socialization of waste banks, waste collection, garbage selection, skills training and evaluation conducted once a month.